2019
DOI: 10.3390/molecules24142525
|View full text |Cite
|
Sign up to set email alerts
|

Endlicheria bracteolata (Meisn.) Essential Oil as a Weapon Against Leishmania amazonensis: In Vitro Assay

Abstract: The difficulties encountered and the numerous side effects present in the treatment of cutaneous leishmaniasis have encouraged the research for new compounds that can complement or replace existing treatment. The growing scientific interest in the study of plants, which are already used in folk remedies, has led our group to test Endlicheria bracteolata essential oil against Leishmania amazonensis. Several species of the Lauraceae family, or their compounds, have relevant antiprotozoal activities Therefore, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…The anti-leishmanial activity of carajurin was evaluated in promastigote forms of L. amazonensis . Viable promastigotes were counted in a Neubauer chamber according to Rottini et al [ 16 ], with the percentage of growth inhibition calculated from the count of viable parasites in relation to the untreated control to determine the values of 50% of inhibitory concentration (IC 50 ). The results showed a significant concentration-dependent decrease ( p < 0.0001) in parasite viability ( Figure 2 ), with IC 50 at 7.96 ± 1.23 μg.mL − 1 (26.4 µM).…”
Section: Resultsmentioning
confidence: 99%
“…The anti-leishmanial activity of carajurin was evaluated in promastigote forms of L. amazonensis . Viable promastigotes were counted in a Neubauer chamber according to Rottini et al [ 16 ], with the percentage of growth inhibition calculated from the count of viable parasites in relation to the untreated control to determine the values of 50% of inhibitory concentration (IC 50 ). The results showed a significant concentration-dependent decrease ( p < 0.0001) in parasite viability ( Figure 2 ), with IC 50 at 7.96 ± 1.23 μg.mL − 1 (26.4 µM).…”
Section: Resultsmentioning
confidence: 99%
“…Incubation took place in a 96-wells plate, in a BOD incubator at 28 °C in LIT medium using a parasite concentration of 10 6 promastigotes/mL. After 24 h, with the aid of the Neubauer chamber and light microscopy [ 46 ], viability was evaluated by counting parasites and the results were used to calculate the IC 50 (50% inhibition of parasite growth) following the formula: IC 50 = (sample counting)/(control counting) ×100 [ 47 ].…”
Section: Methodsmentioning
confidence: 99%
“…Although the study showed varying levels of membrane disruption of tested compounds on different bacteria, the mechanism of action indicates a direct interference on the membrane lipid biosynthesis pathway [35]. Similar ultrastructural alterations were also observed through the accumulation and increase in electron density of lipid droplets in EO-treated parasitic cells via TEM [36,37].…”
Section: Membrane Disruption Activities Of Eosmentioning
confidence: 62%